Toward a Differentiated Assessment of Narcissism in Forensic Contexts: Validating the Narcissistic Admiration and Rivalry Questionnaire–Short Scale (NARQ-S) in a Forensic Sample. (June 2022) - Niemeyer, Lisa M.; Grosz, Michael P.; Jallalvand, Lina; Mota, Simon; Back, Mitja D.
Grandiose narcissism is a multidimensional construct consisting of agentic and antagonistic aspects with markedly distinct correlates and consequences. However, this complexity has not been reflected in how grandiose narcissism is measured and investigated in forensic contexts. To provide a more nuanced picture of narcissism in a forensic context, we harnessed the Narcissistic Admiration and Rivalry Concept. More precisely, we investigated the psychometric properties of the Narcissistic Admiration and Rivalry Questionnaire–Short Scale (NARQ-S) in self- and informant reports of 199 male prisoners. Results confirmed the two-dimensional structure, acceptable internal consistency, moderate self-other agreement, and a differentiated nomological network for the NARQ-S. Admiration and rivalry showed distinct associations with criminal history, institutional misbehaviors, and social status in the group of prisoners. Together, the findings provide initial evidence for the validity and utility of self- and informant reports of the NARQ-S in forensic contexts and its contribution to security and treatment recommendations.